Marital Dissolution and Blood Pressure Reactivity: Evidence for the Specificity of Emotional Intrusion-Hyperarousal and Task-Rated Emotional Difficulty - Sbarra, David A. (Psychosom Med, 2009)
OBJECTIVE: To assess blood pressure (BP) reactivity as recently separated adults completed a laboratory task asking to mentally reflect on their relationship experiences. Marital separations and the experience of divorce are associated with increased risk for early mortality and poor health outcomes. Few studies, however, have investigated the potential psychophysiological mechanisms that may account for these broad-based associations. METHOD: Seventy recently separated or divorced community-dwelling adults (26 men) completed self-report measures of divorce-related psychological adjustment. During a laboratory visit, quasi-continuous BP was assessed across four task periods, including a divorce-specific mental activation task (DMAT). A task-rated emotional difficulty (TRED) index was computed based on participants’ immediate appraisals of the task demands. RESULTS: After accounting for relevant health-related covariates and depressed mood, participants who reported higher degrees of divorce-related emotional intrusion and physical hyperarousal demonstrated significantly elevated resting BP at entry into the study. When assessing change from a within-person control task to the DMAT, a three-way interaction indicated that men reporting high TRED scores evidenced significant increases in BP, whereas men reporting low TRED scores evidenced significant decreases in BP. Women evidenced no significant changes in BP across study periods. CONCLUSIONS: Results suggest that divorce-related emotional intrusion-hyperarousal and real-time ratings of emotional difficulty (when people think about their separation experience) may play a specific role in BP reactivity, especially for men. These data shed new light on the potential mechanisms that may link marital dissolution and poor health.